Autologous Fat Grafting Improves Facial Nerve Function. (8th June 2015) - Klinger, Marco; Lisa, Andrea; Caviggioli, Fabio; Maione, Luca; Murolo, Matteo; Vinci, Valeriano; Klinger, Francesco Maria
Abstract : We describe the case of a 45-year-old male patient who presented a retractile and painful scar in the nasolabial fold due to trauma which determined partial motor impairment of the mouth movements. We subsequently treated him with autologous fat grafting according to Coleman's technique. Clinical assessments were performed at 5 and 14 days and 1, 3, and 6 months after surgical procedure and we observed a progressive release of scar retraction together with an important improvement of pain symptoms. A second procedure was performed 6 months after the previous one. We observed total restoration of mimic movements within one-year follow-up. The case described confirms autologous fat grafting regenerative effect on scar tissue enlightening a possible therapeutic effect on peripheral nerve activity, hypothesizing that its entrapment into scar tissue can determine a partial loss of function.